Laboring and Learning - Abebe, Tatek; Waters, Johanna (Geographies of Children and Young People ;, 2017)
This volume incorporates ground-breaking new academic perspectives on the contributions that children and young people make to societies around the world, with a particular focus on learning and work. The chapters in the volume offer conceptual and empirical insights into how young people learn to labour, and the complex social, spatial, temporal, institutional and relational processes that informs their engagements in daily, generational and social reproduction. The editors have intentionally avoided using the terms 'education' and 'employment' in the title, as this volume is an attempt to capture the multitude of ways, spaces and contexts (not just 'formal') in which learning takes place and work is carried out. Here, learning indicates education in the broadest possible sense, to incorporate not just formal schooling and the acquisition of institutionally recognised academic knowledge and credentials, but also informal learning (including socialization and the on-the-job acquisition of skills that takes place almost imperceptibly, over time). In addition to the theoretical perspectives this volume brings on young people's education and work, other prominent conceptual themes present throughout the work are mobilities, transitions and gender. Following four initial chapters that engage with conceptual issues, the remainder of the volume is divided into two sections, entitled 'spaces of labouring and learning' and 'livelihoods, transitions and social reproduction'. Within these sections, a broad spectrum of empirical chapters demonstrates how young people live, learn and labour in Africa, Asia, Europe and Latin America. These include, among others, geographies of education; interface between migration, learning and livelihoods; cultural politics of human capital formation; schooling and work; citizenship education; families and parenting; socialization and informal education; education-induced migration; processes and practices of inclusion and exclusion in educational institutions; part-time work; domestic work; care work; informal livelihoods; entrepreneurship; social transitions; and a wide range of social, economic, cultural, political (structural) forces that intersect and dissect these topics. As the reader will become aware, there is no such thing as a standard educational or work trajectory, a 'normal' transition or a straight forward relationship between work, education and social reproduction. Indeed, one of the aims of the volume is deliberately to showcase the diversity that young people's lives hold in this regard.